Influenza-Activated ILC1s Contribute to Antiviral Immunity Partially Influenced by Differential GITR Expression - Vashist, Neha; Trittel, Stephanie; Ebensen, Thomas; Chambers, Benedict J.; Guzmán, Carlos A.; Riese, Peggy (Frontiers in Immunology, 2018)
Innate lymphoid cells (ILCs) represent diversified subsets of effector cells as well as immune regulators of mucosal immunity and are classified into group1 ILCs, group 2 ILCs and group 3 ILCs. Group 1 ILCs encompass NK cells and non-NK ILCs (ILC1s) and mediate their functionality via the rapid production of IFN-γ and TNF-α. The current knowledge of ILC1s mainly associates them to inflammatory processes. Much less is known about their regulation during infection and their capacity to interact with cells of the adaptive immune system. The present study dissected the role of ILC1s during early influenza A virus (IAV) infection, thereby revealing their impact on the antiviral response. Exploiting in vitro and in vivo H1N1 infection systems, a cross-talk of ILC1s with cells of the innate and the adaptive immunity was demonstrated, which contributes to anti-influenza immunity. A novel association of ILC1 functionality and the expression of the glucocorticoid-induced TNFR-related protein (GITR) was observed, which hints towards a so far undescribed role of GITR in regulating ILC1 responsiveness. Overexpression of GITR inhibits IFN-γ production by ILC1s, whereas partial reduction of GITR expression can reverse this effect, thereby regulating ILC1 functionality. These new insights into ILC1 biology define potential intervention targets to modulate the functional properties of ILC1s, thus contributing towards the development of new immune interventions against influenza.